2023
DOI: 10.5194/acp-23-2901-2023
|View full text |Cite
|
Sign up to set email alerts
|

Self-lofting of wildfire smoke in the troposphere and stratosphere: simulations and space lidar observations

Abstract: Abstract. Wildfire smoke is known as a highly absorptive aerosol type in the shortwave wavelength range. The absorption of sunlight by optically thick smoke layers results in heating of the ambient air. This heating is translated into self-lofting of the smoke up to more than 1 km in altitude per day. This study aims for a detailed analysis of tropospheric and stratospheric smoke lofting rates based on simulations and observations. The main goal is to demonstrate that radiative heating of intense smoke plumes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…This unique event was discussed in detail by Ohneiser et al (2021). The smoke originated from record-breaking wildfires in central and eastern Siberia, north of Lake Baikal, in the summer of 2019 (Johnson et al, 2021;Ohneiser et al, 2021Ohneiser et al, , 2023Xian et al, 2022b;Sorenson et al, 2022) and affected the ozone layer (Ohneiser et al, 2021;Voosen, 2021;Ansmann et al, 2022). The smoke reached the UTLS height range most probably by self-lofting processes (Ohneiser et al, 2021(Ohneiser et al, , 2023.…”
Section: Mosaic Annual Cycle: Profiles Of Backscatter and Extinction ...mentioning
confidence: 98%
See 3 more Smart Citations
“…This unique event was discussed in detail by Ohneiser et al (2021). The smoke originated from record-breaking wildfires in central and eastern Siberia, north of Lake Baikal, in the summer of 2019 (Johnson et al, 2021;Ohneiser et al, 2021Ohneiser et al, , 2023Xian et al, 2022b;Sorenson et al, 2022) and affected the ozone layer (Ohneiser et al, 2021;Voosen, 2021;Ansmann et al, 2022). The smoke reached the UTLS height range most probably by self-lofting processes (Ohneiser et al, 2021(Ohneiser et al, , 2023.…”
Section: Mosaic Annual Cycle: Profiles Of Backscatter and Extinction ...mentioning
confidence: 98%
“…The ice nucleation efficiency of aged smoke particles is determined by organic material (organic carbon, OC). The black carbon (BC) or soot content is typically 2-3% (Dahlkötter et al, 2014;Yu et al, 2019;Torres et al, 2020;Ohneiser et al, 2023) and has no relevant impact on the ice-nucleating efficiency of aged wildfire smoke particles. Biomass-burning particles also contain humic like substances (HULIS) which represent large macromolecules that could serve as INP at low temperatures of −50 to −70°C (Wang and Knopf, 2011;Wang et al, 2012;Knopf et al, 2018).…”
Section: Arctic Aerosol Of Continental Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Among other studies, self-lofting has been considered in the contexts of individual smoke plumes from large fires (e.g., Herring & Hobbs, 1994;Radke et al, 1990), distinct layers of absorbing haze in the free troposphere (e.g., Haywood et al, 2021), the impacts of absorbing aerosol in volcanic plumes (e.g., Muser et al, 2020), and as a consequence of nuclear conflict (Pausata et al, 2016). As outlined by Boers et al (2010) and Ohneiser et al (2023), the gain in elevation will depend on a range of factors, including the strength of aerosol absorption, the stability of the atmosphere and the length of time before the aerosol is dispersed or removed. In a relatively extreme example, Boers et al (2010) showed self-lofting could raise an optically thick and highly absorbing aerosol layer to the tropopause in 3-4 days Moorthy et al (2016) estimated slightly more modest ascent rates of 1 km per day for absorbing haze in the mid-troposphere above India.…”
mentioning
confidence: 99%